Impact of a cardio-oncology rehabilitation program in patients with breast cancer undergoing cardiotoxic treatment. (14th October 2021) - Oliveira, C C; Matos, M; Azevedo, R; Flores, R; Medeiros, P; Pires, C; Mane, F; Silva, R; Braga, C; Pereira, V H
Abstract: Background: Cancer treatment–related cardiotoxicity (CTrCD) is commonly associated with anthracyclines and anti-HER2 agents which are widely used for the treatment of breast cancer. In order to mitgate CTrCD, exercise-based cardio-oncology rehabilitation (COR) involving a structured exercise program has been proposed. Objectives: To evaluate the impact of a cardiac-rehabilitation program in breast cancer patients submitted to chemotherapy with known cardiotoxicity. Methods: A systematic review was performed. Two databases were searched, PubMed and SCOPUS. All randomized or controlled trials and other prospective studies published between 2000 and March 2020 which evaluate the impact of an aerobic exercise program on cardiorespiratory fitness (CRF), health-related quality of life (QOL), vascular/endothelial function as well as cardiac assessment namely through the evaluation of left ventricular function and cardiac biomarkers in patients undergoing anthracycline and/or anti-HER2 treatments were included. Main results: Fourteen studies were included enrolling 578 breast cancer patients with a mean age of 48.80 years. Regarding the impact of exercise in CRF, 5 studies (n=176) reported a significant improvement of VO2 max. and 4 studies of VO2max./kg (n=137). The peak power output was also improved in 4 studies (n=95) in the exercise-group. Considering the assessment of QOL, 3 studies (n=180) revealed significant differences favoring the exercise-group. The results regarding the evaluation of the LVEF were not clear: 2 studies (n=48) reported a significant decrease on LVEF when compared to baseline at the end of the intervention in both groups, despite the exercise program. However, 2 studies (n=97) showed a significant increase on LVEF in the exercise-group. Three studies (n=82) did not found significant differences in global longitudinal strain between groups. Limited evidence was found in vascular and endothelial functon. In 2 studies (n=50), endothelial function measured by brachial artery flow-mediated dilatation significantly improved in the exercise-group. Two studies (n=98) reported no significant impact of exercise on atenuating the increase of cTnI and BNP levels in the course of chemotherapy. On the other hand, when considering NT-proBNP, an increase in its levels was attenuated in the exercise-group. Conclusions: This study confirms that exercise-based COR seems to be an effective approach to improve several cardiovascular outcomes and quality of life in breast cancer patients. FUNDunding Acknowledgement: Type of funding sources: None.